Design and construction of modern steel railway bridges - Unsworth, John F. (CRC Press, 2017)
"This new edition encompasses current design methods used for steel railway bridges in both SI and Imperial (US Customary) units. It discusses the planning of railway bridges and the appropriate types of bridges based on planning considerations. Modern steel material properties and the loads applied to steel railway bridge superstructures are followed by methods of structural analysis used for modern steel railway bridge design. It also presents the design of axial force members used in truss construction, flexural members used for beam and girder bridges, and the connections used in all bridges are outlined, as well as bridge loads and moving load analysis. It also includes information concerning the fabrication and erection of steel railway superstructures."--Provided by publisher.